The interdependencies of payment and settlement systems - Russo, Daniela (Henry Stewart Talks, 2010)
What are the interdependencies?, System interdependencies, Institution interdependencies, Environment interdependencies, The new 'concerns' stemming from interdependencies, New and faster contagion channels, New sources of liquidity and operational risk, Implications of interdependencies for various stake holders, Implications for systems, participants and central banks, Possible actions for the system operator and central banks